Pengembangan Potensi Atraksi Wisata Gastronomi di Desa Cililin Kabupaten Bandung Barat - Sahabudin, Arfah; Dienaputra, Reiza D.; Nugraha, Awaludin (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 01, Juli 2019, 2019)
In Cililin Village, Cililin District, West Bandung Regency, there are several potentials that can be explored and developed as tourist attractions. One of them is the famous wajit Cililin. Wajit Cililin has been produced for a long time and it is sold in the form of its products. However, there is an interesting side that has not been utilised to be developed, namely the manufacturing process. The purpose of this study is to reveal the potential of Cililin assets to be developed into tourist attractions. The research method used is a qualitative method. Primary data collection is conducted by observation and in-depth interviews. Besides that, a literature study is also conducted. Data analysis uses an interactive model, through three activities carried out simultaneously, namely reduction of data, presentation of data, and conclusion. The results showed that the wajit Cililin manufacturing process has the potential to become a gastronomic tourist attraction and educational tourism, since it has interesting uniqueness. The attraction can only be displayed to tourists by local people who have the skill to process and produce it, hence that the development must involve the local community. Keywords: gastronomic tourism, educational tourism, community based tourism.